Clinical researchSpeeding up coeliac disease diagnosis in cardiological settings - Chicco, Daniela; Taddio, Andrea; Sinagra, Gianfranc; Di Lenarda, Andrea; Ferrara, Fortunato; Moretti, Michele; Martelossi, Stefano; Di Toro, Nicola; Ventura, Alessandro; Not, Tarcisio (Archives of Medical Science, 2010)
Introduction: High prevalence of coeliac disease (CD) has been reported among patients with idiopathic dilated cardiomyopathy (DCM). We evaluated the feasibility and diagnostic accuracy of screening for CD by rapid test of anti-transglutaminase antibodies in the cardiology outpatients’ clinic. Material and methods : We screened the blood samples of 104 patients with DCM, 44 of their first-degree relatives, 63 diseased controls and 101 healthy controls for the presence of anti-transglutaminase antibodies in a drop of whole blood using a rapid assay. This test was compared to the enzyme-linked immunosorbent assay and the anti-endomysium antibody test. Results : Our rapid test was positive in three (2.9%) DCM patients, in one (2%) relative and in one (1%) healthy control. These subjects were positive at both control assays. Two DCM patients had iron-deficient anaemia. The healthy relative was asymptomatic, while the healthy control experienced extreme asthenia. The relative refused intestinal biopsy, while the others showed histological evidence of CD. During the gluten-free diet, the patient with the worst left ventricular ejection fraction (LVEF) underwent heart transplant, and LVEF values improved in the other two. Anaemia and tiredness resolved in all patients. Conclusion : Early detection of CD in a cardiological setting allows prompt treatment with a gluten-free diet of gluten-dependent complaints with potential benefits for the course of DCM.